An evaluation of Forest School for nursery aged children - Cooper, Harriet (2018)
Forest School promotes a child-led approach to education, through frequent learning in an outdoor woodland area. It was developed in the United Kingdom based on the early years practices employed in Denmark. The existing research has begun to generate some evidence of the positive outcomes of Forest School. There appears to be growing confidence in Forest School that is primarily based on non- experimental qualitative research. Therefore, the current research aimed to evaluate the impact of Forest School for nursery aged children, using experimental, outcome-focussed evaluation methods. The study utilised a pragmatic approach, employing a sequential mixed methods study design; the primary focus being the quasi-experimental element of the design, that included 11 children in both the experimental and control groups. The specific research outcomes were developed in collaboration with nursery staff using focus groups, thus, questionnaires were developed to measure social and emotional well-being and communication, pre- and post-intervention. This data is complemented by three case studies of children that participated in Forest School; analysed and presented using activity theory. The quantitative results indicate that both the control group and experimental group made significant gains in social and emotional well-being and communication, suggesting that Forest School did not have a significant effect. The qualitative data, however, highlighted a range of outcomes and provided interesting information regarding the mediating factors which influence the children’s Forest School experiences. The possible reasons for the quantitative outcomes are discussed, including the unique ethos and general outdoor practices used at the nursery setting in which the research took place. The data has also been considered in relation to the methodological weaknesses, such as diffusion of treatment, which may account for the disparity between the data and previous research. Although it cannot be concluded that the Forest School had a significant impact on the children that engaged in the sessions, the current research suggests that the use of general outdoor learning practices and teaching by Forest School trained staff had a positive impact on the social and emotional well-being and communication for all children.